A Journey with Two Mystics: Conversations between a Girardian and a Wattsian - Distefano, Matthew J. (Wipf and Stock Publishers, 2017)
Having a careful ear and an open heart is vital to understanding the big ideas of the Universe. Two friends, Distefano and Machuga, put this on display here, vulnerably exploring some of humanity's most robust topics: what it means to be human, what it means to be saved, what it means to be lost, and what the meaning of life is. And while the authors agree on many things, including the ultimate fate of humanity, they do not necessarily agree on all the details of how we get there. But instead of "agreeing to disagree," they model for their readers what conversations of this variety should look like--agreement with a little pushback, and even some poking fun at one another from time to time.So, as Distefano advises, "take your time and enjoy these discussions." They are transparent and hopeful, refreshingly liberating, and are imbued with complete awe toward the goodness of the Creator and her creation.